2023
DOI: 10.1117/1.oe.62.3.036102
|View full text |Cite
|
Sign up to set email alerts
|

Portable nanosecond laser for handheld laser-induced breakdown spectroscopy instruments

Abstract: The portable laser is indispensable for handheld laser-induced breakdown spectroscopy (LIBS) instruments. We developed a passive, Q-switched pulsed, Nd:YAG laser system with small size and low cost. The maximum pulse energy of the laser was 10 mJ and the pulse duration was <2 ns. The peak power was >5 MW. The laser exhibited very high stability without any cooling system and its relative standard deviation of the pulse energy was <0.2%. The laser was also used as a light source of LIBS to measure the concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…1(a) presents a schematic diagram. A Nd: YAG pulse laser (self-study at Xidian University, 30 China), operating at a wavelength of 1064 nm, pulse energy of 7.8 mJ, repetition rate of 5 Hz, and pulse width of 2 ns, was employed to ablate heat-treated No. 45 steel samples.…”
Section: Methodsmentioning
confidence: 99%
“…1(a) presents a schematic diagram. A Nd: YAG pulse laser (self-study at Xidian University, 30 China), operating at a wavelength of 1064 nm, pulse energy of 7.8 mJ, repetition rate of 5 Hz, and pulse width of 2 ns, was employed to ablate heat-treated No. 45 steel samples.…”
Section: Methodsmentioning
confidence: 99%
“…The SNR can be further improved by optimizing the laser cavity and reducing the splice loss between the optical components. Additionally, a study demonstrated the generation of a portable nanosecond laser with exceptional stability, showcasing a relative standard deviation of the pulse energy of less than 0.2% [41]. Furthermore, insights into the diverse approaches for achieving stable dark pulse generation are provided through investigations conducted on various materials, including topological insulators [42], carbon nanotubes [12], and plasmonic metamaterials [43].…”
Section: Nanosecond Dark Pulse Generationmentioning
confidence: 99%